Prevalence and molecular characterization of Giardia duodenalis in dogs in Israel. (December 2020) - Salant, Harold; Kuzi, Sharon; Navarro, Danielle; Baneth, Gad
Highlights: The fecal PCR prevalence of Giardia was 24.5 % among 302 dogs in Israel. Giardia prevalence was significantly greater in dogs ≤ six months of age (p = 0.001). Giardia prevalence was significantly greater in highly populated shelters in cooler, humid, northern and central-eastern regions (p = 0.000). Giardia prevalence was significantly greater during the winter months (p = 0.003). Dogs with soft/diarrheic stools were significantly more often Giardia positive (p = 0.001). Giardia sp. assemblages C and D were detected. Abstract: Three hundred and two stool samples were collected from municipal shelters and owned dogs in different geographical locations in Israel from December 2016 to September 2017 and examined for Giardia and assemblage type by PCR targeting the 18S rRNA and β-giardin genes. Overall Giardia prevalence was 24.5 % (74/30). Giardia prevalence was 1.9-fold higher in dogs ≤ 6 months old compared to > 6 ≤ 12 months old and older dogs [25/61 (41 %), 18/73 (24.6 %) and 31/166 (18.7 %), respectively, (p = 0.001)], 2.3-fold higher in winter [32/90 (35.5 %)] compared to its prevalence during autumn [15/60 (25 %)], spring [10/62 (16.1 %)] and summer [17/89 (19.1 %), p = 0.003)], and 2.7-fold more frequent among diarrheic dogs [23/43 (53.4 %)] compared to those with formed stools [51/253 (20.1 %)], (p = 0.001)]. The Giardia sp. assemblages detected were C and D. Higher infection rates in young, diarrheic dogs, sampled during winter, and housed in municipal shelters, indicates the need for targeted preventive measures.